2012
DOI: 10.1007/s10103-012-1171-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Er:YAG laser irradiation parameters for debridement of microstructured fixture surfaces of titanium dental implants

Abstract: Er:YAG laser (ErL) irradiation has been reported to be effective for treating peri-implant disease. The present study seeks to evaluate morphological and elemental changes induced on microstructured surfaces of dental endosseous implants by high-pulse-repetition-rate ErL irradiation and to determine the optimal irradiation conditions for debriding contaminated microstructured surfaces. In experiment 1, dual acid-etched microstructured implants were irradiated by ErL (pulse energy, 30-50 mJ/pulse; repetition ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 43 publications
1
53
1
3
Order By: Relevance
“…reported that ErL irradiation accompanied by water spray is capable of titanium surface debridement without temperature rise of, or injuries to, the irradiated titanium surface. Taniguchi et al . clarified the optimal irradiation parameters of ErL using various implants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported that ErL irradiation accompanied by water spray is capable of titanium surface debridement without temperature rise of, or injuries to, the irradiated titanium surface. Taniguchi et al . clarified the optimal irradiation parameters of ErL using various implants.…”
Section: Discussionmentioning
confidence: 99%
“…Various mechanical instruments have been recently used for peri‐implantitis treatment . However, mechanical debridement is associated with significant problems such as physical damage to the implant and the presence of metal or plastic residues . To date, a suitable method to debride contaminated fixture surfaces with calcified deposits, while preserving the microstructure, has not yet been established.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(17,18) PDI uses a specific-wavelength LED or laser irradiation on a photosensitizer (PS). (19)(20)(21)(22)(23)(24)(25) The PS transfers energy to oxygen molecules, producing singlet oxygen ( 1 O 2 ) or reactive oxygen species (ROS). Superoxide radicals, hydroxyl radicals, lipid-derived radicals, and ROS can oxidize proteins, peroxidize lipids, and damage nucleic acids, resulting in bacterial death.…”
Section: Introductionmentioning
confidence: 99%
“…The ErL applications in dental treatments such as operative dentistry [13][14][15][16] , pediatric dentistry 17,18) , endodontics [19][20][21] , periodontics [22][23][24][25][26][27][28][29] , and oral surgery 30,31) have increased in recent years. Furthermore, the use of ErL has also been proposed in implant therapy applications such as the implant placement procedure as well as treatment of peri-implantitis [32][33][34][35][36][37] . On ErL irradiation, two irradiation modes are available: non-contact and contact modes 38) .…”
Section: Introductionmentioning
confidence: 99%